Method for producing carbon-coated sodium fluoride iron phosphate using waste lithium iron phosphate and its use
The method of producing carbon-coated sodium fluorinated iron phosphate from waste lithium iron phosphate addresses the inefficiencies in utilizing waste materials by achieving high recovery and performance in sodium battery cathode materials, reducing waste and costs.
Patent Information
- Application Number
- JP2024506246
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-12-13
- Filing Date
- 2023-12-13
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-12-13
AI Technical Summary
The challenge lies in effectively utilizing waste lithium iron phosphate materials to produce high-performance sodium battery cathode materials, particularly due to the poor electrochemical activity of sodium iron phosphate and the increasing cost and scarcity of lithium resources.
A method involving the production of carbon-coated sodium fluorinated iron phosphate using waste lithium iron phosphate, which includes steps such as reacting waste lithium iron phosphate with an alkaline solution, vacuum roasting with additives, and subsequent mixing with sources of sodium, iron, phosphorus, and fluorine to form carbon-coated sodium iron phosphate fluoride.
This method achieves a high recovery rate of valuable elements, reduces waste generation, and produces a high-performance sodium battery positive electrode material with excellent electrochemical properties and high added value.
Smart Images

Figure 2025501832000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims priority to a Chinese patent application filed on December 13, 2022, bearing application number CN2022116029466 and titled "Method for producing carbon-coated sodium fluoroferric phosphate using waste lithium iron phosphate, and use thereof."
[0002] The present invention relates to the technical field of sodium ion batteries, in particular to a method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate, and its use. [Background technology]
[0003] Due to the abundant reserves of sodium resources and the similar operating principle to lithium-ion batteries, research on sodium-ion batteries has been attracting attention in recent years as one of the new energy storage technologies that is expected to promote the low-cost use and sustainable development of energy storage technology. Polyanion-type compounds are widely studied positive electrode materials with high performance and safety, and the strong covalent bonds in their structures are favorable for stabilizing the structural frame, effectively improving the safety of the electrode during the charge and discharge process.
[0004] Sodium iron phosphate is generally considered to have poor electrochemical activity, but the introduction of fluorine to form sodium iron fluorophosphate can increase the electrochemical activity and improve the voltage platform, making this modification a favorable modification for sodium battery cathode materials.
[0005] Lithium iron phosphate scrap is mainly waste electrode plates generated during the battery manufacturing process, i.e., electrode plates generated when batteries are dismantled after disposal, and according to statistics, the amount of lithium iron phosphate generated annually was 480,000 tons in 2021, and is expected to reach 1 million tons in 2022. How to recycle and utilize these resources is the focus of research.
[0006] Especially with the gradual increase in the price of lithium, sodium batteries are becoming more and more important as a future development trend. Therefore, it is of great importance to utilize discarded lithium battery resources to produce sodium battery materials. With this in mind, the present invention is proposed. Summary of the Invention
[0007] A first object of the present invention is to provide a method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate, which has the following characteristics: low cost, high added value, a short process, a high recovery rate, and excellent electrochemical properties of the produced carbon-coated sodium fluoroiron phosphate.
[0008] A second object of the present invention is to provide a positive electrode piece.
[0009] A third object of the present invention is to provide a sodium ion battery.
[0010] In order to achieve the above objectives of the present invention, the following technical solutions are particularly used:
[0011] In a first aspect, the present invention provides a method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate, comprising the steps of:
[0012] Step (a): mixing and reacting the waste lithium iron phosphate material with an alkaline solution, and then performing solid-liquid separation to obtain an aluminum-containing filtrate and a lithium iron phosphate filtrate.
[0013] Here, the waste lithium iron phosphate material includes electrodes produced by dismantling discarded batteries, and contains lithium iron phosphate and aluminum as main components.
[0014] In step (a), the waste lithium iron phosphate material is reacted with an alkaline solution, in order to react with aluminum in the waste lithium iron phosphate material and dissolve the aluminum.
[0015] In some specific embodiments of the present invention, the reaction in step (a) can be carried out at room temperature and does not require heating, since aluminum reacts with sodium hydroxide to generate a large amount of heat.
[0016] In some specific embodiments of the present invention, in step (a), the reaction is carried out until the bubbles disappear, i.e., no bubbles are generated. Preferably, in step (a), the reaction time is 1-10 h, including but not limited to 2 h, 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h, or any value in between.
[0017] The main component of the aluminum-containing filtrate is metaaluminate ions.
[0018] The main component of the lithium iron phosphate filtration residue is lithium iron phosphate.
[0019] (b) The lithium iron phosphate filter residue, aluminum chloride, and sodium chloride are uniformly mixed, and then vacuum roasted to obtain a roasted material.
[0020] The present invention not only uses aluminum chloride and sodium chloride as roasting additives to realize chlorination roasting, but also reacts aluminum chloride with lithium element to form lithium tetrachloroaluminate, utilizing the principle that the boiling point of lithium tetrachloroaluminate is relatively low, and the lithium element is evaporated while leaving behind the sodium element, and most of the other elements, such as phosphorus, iron, etc., are left behind.
[0021] That is, the main component of the roasted material is sodium iron phosphate.
[0022] During the vacuum roasting process, lithium tetrachloroaluminate escapes with the exhaust gases.
[0023] The vacuum roasting is roasting in a vacuum atmosphere, and the vacuum roasting can be used to lower the boiling point of lithium tetrachloroaluminate, lower the roasting temperature, and sufficiently separate lithium tetrachloroaluminate while reducing energy consumption.
[0024] (c) uniformly mixing the roasted material with at least one of a sodium source, an iron source, and a phosphorus source to obtain a mixed material, to which a fluorine source, a carbon source, and a solvent are added, and the mixed material is uniformly mixed, followed by drying and calcination in order to obtain carbon-coated sodium iron fluorophosphate.
[0025] Among them, the sodium source, iron source and phosphorus source are used for sodium supplementation, iron supplementation and phosphorus supplementation, respectively.
[0026] The carbon source acts as a reducing agent to reduce ferrous iron to trivalent iron, and also acts as a coating agent to coat the surface of sodium iron fluorophosphate to enhance electrical conductivity.
[0027] That is, the carbon-coated sodium iron fluorophosphate obtained in step (c) of the present invention comprises sodium iron fluorophosphate and a carbon coating layer that coats at least a portion of the surface of the sodium iron fluorophosphate.
[0028] The method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate according to the present invention is a short process, low cost, environmentally friendly, and has a high recovery rate of iron and phosphorus, and can produce a high-performance sodium battery cathode material - carbon-coated sodium fluoroiron phosphate.
[0029] In some specific embodiments of the present invention, the mass percentage of carbon in the carbon-coated sodium iron fluorophosphate is 1% to 5%, including but not limited to 2%, 3%, 4%, or any range therebetween.
[0030] Preferably, in step (a), the mass ratio of the waste lithium iron phosphate material to the alkaline solution is 1:5-15, including but not limited to 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, or any value in between.
[0031] Preferably, the alkaline liquid comprises sodium hydroxide solution, which is used to produce sodium carbonate for easy subsequent recovery.
[0032] Preferably, the molar concentration of the alkaline solution is 3 to 5 mol / L, including but not limited to any value of 3.5 mol / L, 4 mol / L, 4.5 mol / L, or any value in the range between the two.
[0033] Preferably, in step (a), the aluminum-containing filtrate is repeatedly utilized until the molar concentration of hydroxide ions therein is less than 0.2 mol / L (including but not limited to any value of 0.15 mol / L, 0.1 mol / L, 0.05 mol / L, 0.01 mol / L or any range therebetween) to obtain an aluminum-containing waste liquid.
[0034] Preferably, step (a) further comprises recovering and treating the aluminium-containing waste liquid to obtain aluminium chloride and sodium carbonate.
[0035] Preferably, the recovery treatment method includes introducing carbon dioxide into the aluminum-containing waste liquid to lower its pH to 9 to 11 (including, but not limited to, any value of 9.3, 9.5, 10, 10.5, 10.8 or any value in a range between these two values), mixing the aluminum hydroxide precipitate with hydrochloric acid to react with each other, and then concentrating and crystallizing the mixture to obtain aluminum chloride, and concentrating and crystallizing the sodium carbonate filtrate to obtain sodium carbonate.
[0036] In some specific embodiments of the present invention, during the process of introducing carbon dioxide, the temperature of the mixed material is 40 to 60°C, including but not limited to any value of 42°C, 45°C, 50°C, 55°C, 58°C, or any value in a range therebetween.
[0037] The aluminum chloride obtained above can be used in step (b).
[0038] The sodium carbonate obtained above can be used as the sodium source in step (c).
[0039] The present invention fully utilizes all the components in the waste lithium iron phosphate material, including aluminum (aluminum foil), which is used to prepare aluminum chloride, sodium hydroxide solution (alkali solution) to prepare sodium carbonate, reducing the generation of waste and saving costs.
[0040] Preferably, in step (b), the molar ratio of lithium element in the lithium iron phosphate filtrate to the aluminum chloride to the sodium chloride is 1:1.2 to 1.5:1.02 to 1.05, for example, 1:1.2:1.02, 1:1.2:1.03, 1:1.2:1.04, 1:1.2:1.05, 1:1.3:1.02, 1:1.3:1.03, 1:1.3:1.04, 1:1.3:1.05, 1:1.4:1.02, 1:1.4:1.03, 1:1.4:1.04, 1:1.4:1.05, 1:1.5:1.02, 1:1.5:1.03, 1:1.5:1.04 or 1:1.5:1.05.
[0041] Preferably, in step (b), the vacuum roasting temperature is 400-600°C, including but not limited to 420°C, 450°C, 500°C, 550°C, 580°C, or any range therebetween, and the vacuum roasting time is 4-6h, including but not limited to 4.5h, 5h, 5.5h, or any range therebetween.
[0042] The vacuum degree of the vacuum roasting is −0.04 to −0.08 MPa, including, but not limited to, any value among −0.05 MPa, −0.06 MPa, and −0.07 MPa, or any value in the range between the two.
[0043] Preferably, in step (b), exhaust gas from the vacuum roasting is collected, mixed with ammonia water, and aluminum precipitation reaction (i.e., aluminum hydroxide precipitation reaction) is carried out, followed by solid-liquid separation, and then the solid material obtained by the solid-liquid separation is sintered to obtain alumina, and the liquid material obtained by the solid-liquid separation is mixed with sodium carbonate to carry out lithium precipitation reaction (i.e., sodium carbonate precipitation reaction), followed by solid-liquid separation to obtain lithium carbonate.
[0044] Among them, the main component of the exhaust gas from vacuum roasting is lithium tetrachloroaluminate. It is mixed with ammonia water, and the aluminum ions react with the ammonia water to produce aluminum hydroxide precipitate. The solid material obtained after solid-liquid separation is the aluminum hydroxide precipitate. It can be calcined to obtain alumina.
[0045] In some specific embodiments of the present invention, the alumina prepared above can be reacted with hydrochloric acid to prepare aluminum chloride, which is used in the subsequent step (b).
[0046] At the same time, the liquid material obtained after the solid-liquid separation contains lithium ions, which can be mixed with sodium carbonate and reacted to obtain lithium carbonate.
[0047] Preferably, the molar concentration of the ammonia water is 0.01 to 0.1 mol / L, and includes, but is not limited to, any value of 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L, 0.08 mol / L, 0.09 mol / L, or any value in a range between these two values.
[0048] In some specific embodiments of the present invention, the molar ratio of nitrogen element in the ammonia water to aluminum element in the exhaust gas is 3.1 to 6:1, including, but not limited to, any value of 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.7:1, 3.9:1, 4:1, 4.5:1, 5:1, 5.5:1, or any value in a range therebetween.
[0049] In some specific embodiments of the present invention, during the vacuum roasting, the exhaust gas from the roasting process is sucked in by an induced draft fan, condensed in a condenser to reduce the temperature to below 150°C, passed through a dust collecting bag, and then absorbed by a water spray to obtain the exhaust gas.
[0050] At present, the price of lithium carbonate is about 500,000 yuan / ton, and the price of sodium iron fluorophosphate is about 85,000 yuan / ton.
[0051] In this way, the present invention can realize complete recovery of each component (including each element, phosphorus, iron, and lithium), recover lithium, and not only obtain lithium carbonate, but also produce sodium ferric fluorophosphate using elements such as iron and phosphorus, which has high added value of the product.
[0052] Preferably, in the aluminum precipitation reaction, the temperature of the mixed material is 40-80° C., including but not limited to any value of 45° C., 50° C., 55° C., 60° C., 65° C., 70° C., 75° C., or any value in between. The time of the aluminum precipitation reaction is 1-3 h, including but not limited to any value of 1.5 h, 2 h, 2.5 h, or any value in between.
[0053] Preferably, in the lithium precipitation reaction, the temperature of the mixed material is 60-90° C., including but not limited to 65° C., 70° C., 75° C., 80° C., 85° C., or any range therebetween. The time of the lithium precipitation reaction is 1-3 h, including but not limited to 1.5 h, 2 h, 2.5 h, or any range therebetween.
[0054] Preferably, in step (c), before mixing the roasted material with at least one of a sodium source, an iron source, and a phosphorus source, the contents of Na element, Fe element, and P element in the roasted material are detected, and the mixed material is blended so that a molar ratio of Na element, Fe element, and P element in the mixed material is 0.95-0.98:1:1.02-1.05. Among them, the molar ratio is, for example, 0.95:1:1.02, 0.96:1:1.02, 0.97:1:1.02, 0.98:1:1.02, 0.95:1:1.03, 0.96:1:1.03, 0.97:1:1.03, 0.98:1:1.03, 0.95:1:1.04, 0.96:1:1.04, 0.97:1:1.04, 0.98:1:1.04, 0.95:1:1.05, 0.96:1:1.05, 0.97:1:1.05 or 0.98:1:1.05.
[0055] That is, the roasted material is sampled and detected, the contents of Na, Fe, and P elements therein are detected, the molar ratio of Na:Fe:P in the roasted material is calculated, and at least one raw material selected from a sodium source, an iron source, and a phosphorus source (one, two, or three of them can be added based on the calculation result) is added so that the molar ratio of Na:Fe:P in the roasted material is 0.95 to 0.98:1:1.02 to 1.05.
[0056] Preferably, the sodium source comprises at least one of sodium carbonate, sodium bicarbonate, and sodium acetate, the iron source comprises at least one of red iron oxide, iron (II) oxalate, and iron acetate, and the phosphorus source comprises at least one of phosphoric acid, ammonium monohydrogen phosphate, and ammonium dihydrogen phosphate.
[0057] Preferably, in step (c), the fluoride source comprises sodium fluoride.
[0058] Preferably, the molar ratio of the fluorine source to Fe element in the mixed material is 0.95 to 0.98:1, including but not limited to 0.95:1, 0.96:1, 0.97:1, 0.98:1, or any value in between.
[0059] Preferably, in step (c), the carbon source comprises at least one of glucose, sucrose, polyethylene glycol, and starch.
[0060] Preferably, the mass ratio of the carbon source to the roasted material is 0.2 to 0.3:1, including, but not limited to, any value of 0.21:1, 0.22:1, 0.23:1, 0.24:1, 0.25:1, 0.26:1, 0.27:1, 0.28:1, 0.29:1, or any value in a range therebetween.
[0061] Preferably, in step (c), the solvent comprises water and / or an organic solvent, more preferably water.
[0062] In some specific embodiments of the present invention, the organic solvent can be any conventional volatile solvent, such as, but not limited to, ethanol, propanol, and ethylene glycol.
[0063] Preferably, in step (c), the fluorine source, carbon source and solvent are added and then crushed to mix uniformly.
[0064] More preferably, the solid particles in the mixed slurry are crushed until the particle diameter is 200 to 400 nm, and the particle diameter includes, but is not limited to, any value of 220 nm, 250 nm, 300 nm, 350 nm, 380 nm, or any value in a range between the two.
[0065] Preferably, in step (c), said drying comprises spray drying.
[0066] More preferably, the particle size of the drying material obtained by the spray drying is 10 to 30 μm, including, but not limited to, any value of 12 μm, 15 μm, 20 μm, 25 μm, 28 μm, or any value in a range between the two.
[0067] In some specific embodiments of the present invention, the moisture content in the desiccant obtained by spray drying is less than 0.5 wt%, including but not limited to any of the following values: 0.4 wt%, 0.3 wt%, 0.2 wt%, 0.1 wt%, or any range therebetween.
[0068] Preferably, in step (c), the calcination temperature is 550-650° C., including but not limited to 560° C., 570° C., 580° C., 590° C., 600° C., 610° C., 620° C., 630° C., 640° C., or any range therebetween. The calcination incubation time is 4-6 h, including but not limited to 4.5 h, 5 h, 5.5 h, or any range therebetween.
[0069] In some specific embodiments of the present invention, in step (c), the heating rate in the calcination is 100-150°C / h, including but not limited to 110°C / h, 120°C / h, 130°C / h, 140°C / h, or any value in a range therebetween.
[0070] In some specific embodiments of the present invention, in step (c), after the calcination is completed, the material temperature is lowered to 100° C. or less before being discharged.
[0071] In some specific embodiments of the present invention, in step (c), the calcination is carried out under an inert atmosphere, such as, but not limited to, a nitrogen atmosphere and / or an argon atmosphere. Preferably, the oxygen content in the inert atmosphere is less than 5 ppm, including, but not limited to, any of the following values: 4 ppm, 3 ppm, 2 ppm, 1 ppm, or any range therebetween. Preferably, the humidity of the inert atmosphere is less than 3%, including, but not limited to, any of the following values: 2%, 1%, 0.5%, or any range therebetween.
[0072] In some specific embodiments of the present invention, in step (c), an induced draft fan is connected to the temperature-raising zone of the calcination to exhaust the exhaust gas in the temperature-raising zone.
[0073] Preferably, step (c) further comprises the steps of crushing, sieving and removing iron, successively, after said calcination.
[0074] In some specific embodiments of the present invention, the grinding can be performed by any conventional grinding method, such as, but not limited to, airflow grinding.
[0075] In some specific embodiments of the present invention, the sieving can be performed by any conventional sieving method, for example, but not limited to, sieving using an ultrasonic vibrating screen.
[0076] In some specific embodiments of the present invention, the iron removal can be performed by any conventional iron removal method, such as, but not limited to, an electromagnetic iron remover, and preferably, the iron removal is stopped when the magnetic material in the material is less than 1 ppm, including, but not limited to, 0.8 ppm, 0.5 ppm, 0.3 ppm, 0.1 ppm, or any value in between.
[0077] In some specific embodiments of the present invention, after the iron removal, the method further comprises a step of vacuum packaging in a temperature and humidity chamber.
[0078] Preferably, the carbon-coated sodium iron fluorophosphate subjected to the pulverization and sieving has a D50 particle size of 0.5 to 2 μm.
[0079] In a second aspect, the present invention provides a positive electrode piece made of carbon-coated sodium ferrous fluorophosphate produced by the method for producing carbon-coated sodium ferrous fluorophosphate using waste lithium iron phosphate as described above.
[0080] In a third aspect, the present invention provides a sodium-ion battery comprising the positive electrode piece described above.
[0081] The sodium ion battery is low cost and has excellent electrochemical properties. Effect of the Invention
[0082] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0083] (1) The method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate according to the present invention involves a short process, is low cost, has a high recovery rate of iron and phosphorus, and produces carbon-coated sodium fluoroiron phosphate with a low impurity content and excellent electrochemical properties.
[0084] (2) The method for producing carbon-coated sodium ferric fluorophosphate using waste lithium ferric phosphate according to the present invention can completely recover each element of phosphorus, iron, and lithium, recover lithium to obtain lithium carbonate, and produce sodium ferric fluorophosphate using elements such as iron and phosphorus, resulting in high added value of the product.
[0085] (3) The method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate according to the present invention can fully utilize the exhaust gas and waste liquid generated in the recovery process, thereby reducing the generation of waste, reducing costs, and avoiding the waste of resources. [Brief description of the drawings]
[0086] In order to more clearly describe the specific embodiments of the present invention or the technical solutions in the prior art, the following briefly describes the drawings used for describing the specific embodiments or the prior art. Obviously, the drawings described below are some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without creative efforts. [Figure 1] FIG. 2 is a 0.1C charge / discharge curve diagram of the carbon-coated sodium iron fluorophosphate prepared in Example 1 according to the present invention. [Diagram 2] 1 is an SEM image of carbon-coated sodium iron fluorophosphate produced in Example 1 according to the present invention. [Diagram 3] 1 is an XRD image of the carbon-coated sodium iron fluorophosphate produced in Example 1 according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0087] The technical solutions of the present invention will be described below clearly and completely with reference to the drawings and specific embodiments. Those skilled in the art should consider that the examples described below are only some examples of the present invention, not all examples, and are only for illustrating the present invention and not for limiting the scope of the present invention. Based on the examples in the present invention, all other examples obtained by those skilled in the art without creative labor belong to the patent scope of the present invention. In the examples, the specific conditions are not specified, and the procedures are carried out according to normal conditions or conditions recommended by the manufacturer. The reagents or equipment used are all general products purchased commercially unless the manufacturer is specified. EXAMPLES
[0088] Example 1 The method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate according to this embodiment includes the following steps. (1) 10 kg of waste lithium iron phosphate material is mixed with 100 kg of sodium hydroxide solution with a molar concentration of 4 mol / L to react with each other, dissolve aluminum, and react until bubbles disappear. The reaction is then terminated (reaction time is 3.5 h), and then filtered to obtain a first aluminum-containing filtrate and a lithium iron phosphate filtrate residue. Here, the impurities in the waste lithium iron phosphate material are mainly aluminum foil, and the ratio is 20.5 mass%. The detection results of the content of each element in the first aluminum-containing filtrate (volume: 80.05 L) produced above are shown in Table 1 below.
[0089] [Table 1]
[0090] (2) The aluminum-containing filtrate obtained in step (1) is reused, and further mixed with 10 kg of waste lithium iron phosphate material to react, and when hydroxide ion is consumed to a molar concentration of less than 0.18 mol / L, it is filtered, and the obtained second aluminum-containing filtrate (volume is 76.46 L) is sampled and detected, and the results are shown in Table 2.
[0091] [Table 2]
[0092] Carbon dioxide was introduced into the second aluminum-containing filtrate at a temperature of 50°C, and the pH of the filtrate was then measured online. When the pH dropped to 10.1, the introduction of carbon dioxide gas was stopped and the mixture was stirred for another 50 minutes to allow the reaction to proceed, and then filtered to obtain an aluminum hydroxide precipitate and a sodium carbonate filtrate.
[0093] The above aluminum hydroxide precipitate is dissolved in hydrochloric acid and the end pH is maintained at 1.3 to obtain an aluminum chloride solution, which is then concentrated and crystallized to obtain aluminum chloride crystals with a measured purity of 99.4 wt % and is ready for use (used in step (3) below).
[0094] The sodium carbonate filtrate obtained above is concentrated and crystallized to obtain sodium carbonate. The sodium carbonate is concentrated until the Baume degree reaches 52, and then cooled for 12 hours to crystallize. When the end temperature reaches 25°C, the crystallized product is centrifuged and baked. The purity is measured and found to be 99.2 wt%. The product is used as the sodium source (to be used in step (4) below).
[0095] (3) Add aluminum chloride and sodium chloride to the lithium iron phosphate filter residue obtained in step (1) so that the molar ratio of lithium element to aluminum chloride to sodium chloride in the lithium iron phosphate filter residue is 1:1.35:1.045, mix uniformly, and then roast at a vacuum degree of -0.065 MPa and a temperature of 500°C for 5 hours to react, thereby obtaining a roasted material.
[0096] During roasting, the exhaust gas from roasting is sucked in using an induced draft fan, condensed in a condenser to a temperature of 135°C, passed through a dust collection bag, and then absorbed with a water spray to obtain the exhaust gas.
[0097] Then, add 0.08 mol / L ammonia water solution (the molar ratio of nitrogen element in ammonia water to aluminum element in the exhaust gas is 3.5:1) to the above exhaust gas, and after stirring, react at 60°C for 1.5 hours, control the end point pH to 7.9, then filter and wash, and obtain precipitate, sinter at 650°C, calcination time is 7 hours, obtain alumina. The detection data of alumina is shown in Table 3.
[0098] Then, sodium carbonate is added to the filtrate obtained by the above filtration, and the end point pH is controlled to 10.5, the reaction temperature is controlled to 75°C, and the reaction time is controlled to 1h. After that, it is filtered and washed to obtain industrial grade lithium carbonate. Its purity is detected to be 99.35%. The detection data of industrial grade lithium carbonate is shown in Table 4.
[0099] [Table 3]
[0100] [Table 4]
[0101] (4) The content of each element in the roasted material obtained in step (3) was detected, and the detection results are shown in Table 5 below.
[0102] [Table 5]
[0103] As a result of calculation, it was found that the molar ratio of Na:Fe:P in the above roasted material was 0.954:1:0.989. Therefore, it is necessary to add a sodium source and a phosphorus source. Sodium carbonate and ammonium dihydrogen phosphate were added to the roasted material to maintain the molar ratio of Na, Fe, and P at 0.975:1:1.04, and the mixture was uniformly mixed to obtain a mixed material. Then, sodium fluoride, a carbon source, and pure water were added to the mixed material and stirred to form a slurry. Glucose and sucrose with a mass ratio of 1:0.3 were used as carbon sources, and the mass of the carbon source (the sum of the masses of glucose and sucrose) was 0.25 times the mass of the above roasted material. The molar ratio of sodium fluoride to iron element in the above mixed material was 0.97:1.
[0104] The slurry material thus stirred was then crushed until the particle diameter of the solid particles in the slurry was 285 nm, and then spray-dried to obtain a spray-dried material with a particle diameter of 21.7 μm and a moisture content of less than 0.5 wt%.
[0105] The spray-dried material was then calcined to obtain a calcined material. Here, the heating rate was set to 120°C / h. After that, the material was kept at 600°C for 5 hours, and was discharged when the temperature of the material was lowered to less than 100°C. Nitrogen gas was introduced during calcination to maintain the oxygen gas content in the calcination furnace at less than 5 ppm and the humidity at less than 3%. An induced draft fan was connected to the temperature-raising region to exhaust the exhaust gas in the temperature-raising region.
[0106] The calcined material was jet-milled until the particle size of the material was 1.4 μm. It was then sieved using a 100-mesh ultrasonic vibrating screen. It was then de-ironized using an electromagnetic iron remover, and when the magnetic substance in the material was less than 1 ppm, the iron removal was stopped. It was then vacuum-packed in a temperature- and humidity-controlled room to obtain carbon-coated sodium iron fluorophosphate that can be used as a positive electrode material for sodium batteries.
[0107] The detection data for each item of the carbon-coated sodium iron fluorophosphate produced in this example are shown in Table 6 below.
[0108] [Table 6]
[0109] Here, the compressed density is measured at 3T pressure.
[0110] Powder resistivity was measured using the four-probe method at a pressure of 10 MPa.
[0111] For the measurement of electrical specificity, a 0.3 Ah soft-pack battery was used, the positive electrode current collector was carbon-coated aluminum foil, the positive electrode composition was a mass ratio of 88:7:5 substrate, SP, and PVDF, the plate was compressed to 2.35 g / mL, the electrolyte was sodium hexafluorophosphate, the negative electrode current collector was aluminum foil, and the negative electrode was hard carbon, which was obtained by pretreating asphalt and then baking it at high temperature. The measurement voltage range was 2.0 to 4.0 V.
[0112] Free sodium was measured by adding 100 g of pure water to 10 g of material, stirring at 25° C. for 30 min, filtering, and measuring sodium ions in the filtrate using ICP.
[0113] Fluorine was measured using a fluoride ion selective electrode.
[0114] To measure iron elution, 100 mL of hydrochloric acid with a molar concentration of 0.05 mol / L is added to 10 g of material, the material is immersed at a temperature of 40°C for 30 minutes, and then filtered. The iron content of the filtrate is measured.
[0115] The 0.1C charge-discharge curve is shown in Figure 1. It can be seen from Figure 1 that the carbon-coated sodium iron fluorophosphate prepared in this example has a clear discharge platform and small polarization.
[0116] FIG. 2 shows an SEM image of the carbon-coated sodium iron fluorophosphate produced above.
[0117] The XRD image of the carbon-coated sodium iron fluorophosphate prepared above is shown in FIG.
[0118] Example 2 The method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate according to this embodiment was the same as that of Example 1, except that in step (4), the carbon source was changed to polyethylene glycol, and the mass of the polyethylene glycol was 0.3 times the mass of the roasted material.
[0119] Example 3 The method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate according to this embodiment was the same as that of Example 1, except that in step (4), the carbon source was changed to starch, and the mass of the starch was 0.2 times the mass of the roasted material.
[0120] Comparative Example 1 The method for producing carbon-coated sodium iron phosphate using waste lithium iron phosphate according to this comparative example was the same as that of Example 1, except that sodium fluoride was not added in step (4). That is, the product produced in this comparative example was carbon-coated sodium iron phosphate.
[0121] Comparative Example 2 The method for producing sodium iron fluorophosphate using waste lithium iron phosphate according to this comparative example was the same as that of Example 1, except that in step (4), instead of adding a carbon source, a N2+H2 mixed gas was introduced during calcination for reduction. In other words, the product produced in this comparative example is sodium iron fluorophosphate with a small carbon coating layer on the surface. The electrical characteristics of the carbon-coated sodium iron phosphate produced in Comparative Example 1 and the sodium iron fluorophosphate produced in Comparative Example 2 were measured (the detection method was the same as in Example 1), and the results are shown in Table 7.
[0122] [Table 7]
[0123] As a result of comparing the test results of the electrical characteristics of Example 1 and Comparative Examples 1 and 2, it was found that Example 1 was superior in capacity, initial discharge efficiency, and cycle characteristics.
[0124] Specifically, compared to Comparative Example 1, Example 1 introduces fluorine ions, which can increase the capacity. In addition, the introduction of fluorine effectively forms doping, forms a eutectic effect, and can improve ionic conductivity, thereby increasing the capacity. Sodium iron fluorophosphate has a higher sodium content than sodium iron phosphate, and therefore the theoretical capacity is also increased.
[0125] Compared with Comparative Example 2, the electrical conductivity of the polyanionic sodium battery material itself is poor, so the appropriate carbon coating in Example 1 is effective in improving the electronic conductivity of the material, and the appropriate carbon coating can also prevent particle growth, make the primary particle size of the particles more uniform, effectively avoid particle growth, and improve the capacity and cycle characteristics.
[0126] As described above, the carbon-coated sodium iron fluorophosphate produced by the method for producing carbon-coated sodium iron fluorophosphate using waste lithium iron phosphate according to the present invention has excellent electrochemical properties and is useful as a positive electrode material for sodium batteries.
[0127] Although the present invention has been illustrated and described by specific embodiments, it should be recognized that the above embodiments are only used to explain the technical means of the present invention, and are not limited thereto. Those skilled in the art can modify the technical means described in the above embodiments or replace some or all of the technical features with equivalents without departing from the spirit and scope of the present invention, and these modifications or replacements should be understood as not causing the essence of the corresponding technical means to depart from the scope of the technical means of the embodiments of the present invention, which means that the appended claims include all these replacements and modifications that belong to the scope of the present invention.
Claims
1. A method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate, comprising the steps of: (a) mixing and reacting the waste lithium iron phosphate material with an alkaline solution, and then subjecting the mixture to solid-liquid separation to obtain an aluminum-containing filtrate and a lithium iron phosphate filtrate residue; (b) uniformly mixing the lithium iron phosphate filter residue, aluminum chloride, and sodium chloride, and then subjecting the mixture to vacuum roasting to obtain a roasted material; and (c) uniformly mixing the roasted material with at least one of a sodium source, an iron source, and a phosphorus source to obtain a mixed material, to which a fluorine source, a carbon source, and a solvent are added, and the mixed material is uniformly mixed, followed by drying and calcination to obtain carbon-coated sodium iron fluorophosphate.
2. In step (a), the mass ratio of the waste lithium iron phosphate material to the alkaline liquid is 1:5-15; Preferably, the alkaline liquid comprises a sodium hydroxide solution; The method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate according to claim 1, characterized in that the molar concentration of the alkaline solution is preferably 3 to 5 mol / L.
3. In step (a), the aluminum-containing filtrate is repeatedly used until the molar concentration of hydroxide ions therein is less than 0.2 mol / L to obtain an aluminum-containing waste liquid; Preferably, step (a) further comprises recovering and treating the aluminum-containing waste liquid to obtain aluminum chloride and sodium carbonate; The method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate according to claim 2, characterized in that the recovery treatment method preferably includes the steps of introducing carbon dioxide into the aluminum-containing waste liquid to lower the pH of the waste liquid to 9 to 11, followed by solid-liquid separation to obtain an aluminum hydroxide precipitate and a sodium carbonate filtrate, mixing the aluminum hydroxide precipitate with hydrochloric acid to cause a reaction, and then concentrating and crystallizing the mixture to obtain aluminum chloride, and concentrating and crystallizing the sodium carbonate filtrate to obtain sodium carbonate.
4. In step (b), the molar ratio of lithium element in the lithium iron phosphate filtration residue, the aluminum chloride, and the sodium chloride is 1:1.2-1.5:1.02-1.05; Preferably, in step (b), the temperature of the vacuum roasting is 400-600° C., and the time of the vacuum roasting is 4-6 h; The method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate according to claim 1, characterized in that the vacuum roasting is performed at a vacuum degree of -0.04 to -0.08 MPa.
5. In step (b), exhaust gas from the vacuum roasting is collected, mixed with ammonia water, and subjected to aluminum precipitation reaction, followed by solid-liquid separation; the solid material obtained by the solid-liquid separation is then sintered to obtain alumina; the liquid material obtained by the solid-liquid separation is mixed with sodium carbonate to perform lithium precipitation reaction, followed by solid-liquid separation to obtain lithium carbonate; Preferably, the molar concentration of the ammonia water is 0.01 to 0.1 mol / L, Preferably, in the aluminum precipitation reaction, the temperature of the mixed material is 40-80° C., and the time of the aluminum precipitation reaction is 1-3 h; The method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate according to claim 1, characterized in that in the lithium precipitation reaction, the temperature of the mixed material is preferably 60 to 90°C, and the time of the lithium precipitation reaction is 1 to 3 hours.
6. In step (c), before mixing the roasted material with at least one of a sodium source, an iron source, and a phosphorus source, the contents of Na, Fe, and P in the roasted material are detected, and the roasted material is mixed so that a molar ratio of Na, Fe, and P in the mixed material is 0.95 to 0.98:1:1.02 to 1.05; The method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate according to claim 1, characterized in that the sodium source preferably contains at least one of sodium carbonate, sodium bicarbonate, and sodium acetate, the iron source preferably contains at least one of red iron oxide, iron (II) oxalate, and iron acetate, and the phosphorus source preferably contains at least one of phosphoric acid, ammonium monohydrogen phosphate, and ammonium dihydrogen phosphate.
7. In step (c), the fluorine source comprises sodium fluoride; Preferably, the molar ratio of the fluorine source to the Fe element in the mixed material is 0.95 to 0.98:1; Preferably, in step (c), the carbon source comprises at least one of glucose, sucrose, polyethylene glycol, and starch; Preferably, the mass ratio of the carbon source to the roasted material is 0.2 to 0.3:1; The method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate according to claim 1, characterized in that in step (c), the solvent preferably comprises water and / or an organic solvent.
8. In step (c), the fluorine source, the carbon source, and the solvent are added, and then crushed and mixed uniformly, preferably until the particle diameter of the solid particles in the mixed slurry is 200 to 400 nm; Preferably, in step (c), the drying comprises spray drying, more preferably the particle size of the drying material obtained by the spray drying is 10 to 30 μm; Preferably, in step (c), the calcination temperature is 550-650° C. and the calcination incubation time is 4-6 h; Preferably, step (c) comprises the steps of crushing, sieving and removing iron after said calcination, The method for producing carbon-coated sodium fluoroiron phosphate using waste lithium iron phosphate according to claim 1, characterized in that the carbon-coated sodium fluoroiron phosphate subjected to the pulverization and sieving has a D50 particle size of 0.5 to 2 μm.
9. A positive electrode piece made of carbon-coated sodium iron fluorophosphate produced by the method for producing carbon-coated sodium iron fluorophosphate using mainly the waste lithium iron phosphate according to any one of claims 1 to 8.
10. A sodium ion battery comprising the positive electrode piece of claim 9.
Citation Information
Patent Citations
Method for preparing lithium iron phosphate by recycling waste batteries
CN113526482A
Carbon-coated sodium ferric fluorophosphate material as well as preparation method and application thereof
CN114242968A
Sodium ferrous fluorophosphate-graphitized carbon-amorphous carbon composite positive electrode material and preparation and application thereof
CN115275125A
Aluminum foil and positive electrode active material separating method
JP2011154833A
Method of treating lithiferous ores to recover lithium as lithium chloride
US2561439A